Little Constellation : Contemporary Art in geo-cultural micro-areas and small States of Europe. - Canarezza, Rita; Coro, Pier Paolo; Daolio, Roberto; Racanovic, Svetlana; Michaelidou, Louli; Mallart i Casamajor, Lluis & Domingo i Coll, Jordi; Stolz, Noah; Castiglioni, Alessandro (Milano : Mousse Publishing, 2010)
Albani, Pier Giorgio & Mussoni, Lorella ; Akimov, Danil ; Berg Sigmarsson, Sigtryggur ; Bühler, Barbara ; Geyer, Barbara ; Lagator, Irena ; Magnadottir, Ingibjörg ; Mangion, Mark & Portelli, Pierre ; Uranova, Axsinja ; et al.
Book : Research Project about the practice of making art experienced today in certain geo-cultural micro-areas and small states of Europe; this book collects and illustrates the main steps in this journey through texts, images, video interviews, meetings, workshops, a website and exhibitions.
Engels
Italiaans
boek